Analisis Keterkaitan Produksi Kunyit di Indonesia dan Faktor-Faktor yang Mempengaruhinya - Nurul Husniyati Listyana (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This study aims to analyze the relationship between turmeric production and the factors that influence it. The variables used in this study include production, export, import, inflation, land area, and exchange rate. This research is a descriptive research. The data in this study are data obtained from the Central Bureau of Statistics, Ministry of Agriculture, Ministry of Trade and Bank Indonesia. Research data were analyzed using regression analysis. The data used are secondary data for a period of 15 years namely 2002-2016. The results showed that the variables of export, import, inflation, land area and exchange rate together significantly influence the production of turmeric. Partially, the export, inflation and land area variables significantly influence the production of turmeric. While the import and exchange rate variables have no significant effect on turmeric production.